1976
DOI: 10.1007/bf02644080
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of toughness in AISI 4340 alloy steel austenitized at low and high temperatures

Abstract: It has been reported for as-quenched AISI 4340 s~eel that high temperature austenitizing treatments at 1200°C, instead of conventional heattreatment at 870°C, result in a twofold increase in fracture toughness,. ~Ic'• but a decrease in Charpy impact energy. This paper seeks to find an explanation for this discrepancy in Charpy and fracture toughness data in terms of the difference between Kic and impact tests. It is shown that the observed behavior is independent of shear lip energy and strain rate effects, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
86
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(89 citation statements)
references
References 15 publications
2
86
1
Order By: Relevance
“…The specimens that showed grain size dependence of the impact toughness arranged by Hui 7) were tempered at 673 K, which is not inconsistent with the present results. It is reported by Ritchie et al 8,9) that for the as-quenched and 473 K tempered martensitic steels, the impact Charpy energy decreases by about 78 J as PAG size increases from about 20 to 200 µm. Therefore, it might be difficult to observe the PAG size effect on the impact toughness in the present plain martensitic steels.…”
Section: Microstructure and Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The specimens that showed grain size dependence of the impact toughness arranged by Hui 7) were tempered at 673 K, which is not inconsistent with the present results. It is reported by Ritchie et al 8,9) that for the as-quenched and 473 K tempered martensitic steels, the impact Charpy energy decreases by about 78 J as PAG size increases from about 20 to 200 µm. Therefore, it might be difficult to observe the PAG size effect on the impact toughness in the present plain martensitic steels.…”
Section: Microstructure and Mechanical Propertiesmentioning
confidence: 99%
“…Hui et al 7) investigated the effect of prior austenite grain (PAG) size on impact toughness, where they reported the enhancement in toughness and ductility of fine-grained 1.08Cr0.39C martensitic steel tempered at 673 K. Decrease in the Charpy impact energy in accordance with the increase in PAG size was observed in the as-quenched and 473 K tempered martensitic steel. 8,9) Kawasaki et al 10) used an induction heating method, which makes use of the rapid heating process in grain growth or carbide forming kinetics, 11) in austenitizing and tempering of 0.58%C steel to investigate the mechanical properties in relation to the microstructures, and they reported that the finer microstructure gives rise to enhancement in ductility, impact toughness and so forth. However, in tempered martensitic steels, the grain size effect could be diminished by the carbide precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in low alloy 4340-type steels, it has been shown that"sharp crack" Krc toughness can be increased as the coarseness of the microstructure is increased by raising the austenitizing temperature, while the "rounded-notch" Charpy values actually decreased (6,7), a result 1 independent of loading rate and fracture mode (S-7). Another example involves wrought and cast steels, for which Charpy V-notch measurements imp 1 i ed an inferior toughness of cast a 11 oys, whereas Krc values remained unchanged (8).…”
mentioning
confidence: 97%
“…Composites made from PyC-coated graphite, however, exhibit slightly higher toughness values, ranging from ϳ1.3 to 1.6 MPa͌m. 5,7 Because the fracture resistance is a critical property of these materials, there is a often a 12 and PyC-coated graphite 5 using saw-cut notches (notch root radii unreported), in place of precracks, yielded erroneously high toughness values of 2.5 and 3.9 MPa͌m, respectively, a common trend seen in most ductile 13 and brittle 14 materials. Due to its high fatigue resistance, however, fatigue precracking is a difficult and costly procedure for PyC and its composites.…”
Section: Introductionmentioning
confidence: 97%